Influence of Residual Platelet Count on Routine Coagulation, Factor VIII, and Factor IX Testing in Postfreeze-Thaw Samples - Lippi, Giuseppe; Rossi, Rossana; Ippolito, Luigi; Zobbi, Valentina; Azzi, Donata; Pipitone, Silvia; Favaloro, Emmanuel J.; Funk, Dorothy M. Adcock (Seminars in Thrombosis and Hemostasis, 2013)
The use of frozen-thawed samples rather than fresh samples for specialized coagulation testing is becoming commonplace, thereby creating novel risks that may jeopardize the quality of hemostasis testing. Residual platelets (PLTs) in frozen plasma are most critical as freezing-induced activation and injury may impair routine and specialized testing after thawing. The aim of this study was to verify the impact of postcentrifugation PLT count in postfreeze-thawed samples on activated partial thromboplastin time (APTT), prothrombin time (PT), fibrinogen, factor VIII (FVIII) activity testing, and factor IX (FIX) activity testing. These parameters were herein assessed in postfreeze-thaw paired plasma samples collected from 15 healthy volunteers and subjected to 4 different centrifugation forces (i.e., 3,000, 1,500, 1,000, and 500g), using data obtained with centrifugation force of 1,500g as the gold standard, in agreement with current recommendations. Compared with reference samples, PLT counts in fresh aliquots were indistinguishable in specimens centrifuged at 1,000g, significantly lower in those centrifuged at 3,000g and significantly higher in those centrifuged at 500g. In all cases except samples centrifuged at 3,000g, the PLT count was significantly decreased in postfreeze-thaw compared with paired fresh specimens. In postfreeze-thaw plasma, APTT was not influenced by residual PLT count. The results of PT and fibrinogen were consistently altered in samples centrifuged at 1,000 and 500g, though the correlation with the reference measures remained clinically acceptable. Data obtained for FVIII and FIX activities revealed a positive bias in all postfreeze-thaw plasmas, achieving statistical significance in samples centrifuged at 3,000g. We conclude that alteration of centrifuge speeds away from the recommended 1,500g may influence the level of residual PLTs in sample centrifuged at lower speeds such as 500g, and therefore may make these specimens unsuitable for hemostasis testing in postfreeze-thawed plasma samples. In addition, although the changes seen in FVIII and FIX in samples centrifuged at 3,000g may reflect non-PLT–related effects, such changes should also be considered in this setting.
Keywords: preanalytical variability; coagulation; hemostasis; centrifugation; freezing